ANCAMAN BUNUH DIRI PADA ANAK USIA SEKOLAH DASAR: URGENSI DETEKSI DINI DAN INTERVENSI EKOLOGIS - Rivie Selvianti; Mhd Ricky Ardiansyah Putra; Annisa Carolin Br Sebayang; Lode Wijk Pandapotan Girsang; Irda Yusepa (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
The phenomenon of suicide has become a serious threat to global public health, with a shifting trend now affecting primary school-aged children. This study aims to explore the complex dynamics behind suicidal behavior in children through an ecological perspective and identify risk factors as well as prevention efforts. The method employed is a literature review with a descriptive-qualitative approach to integrate various developmental theories and actual case report data. The results of the study indicate that destructive actions in children are the result of systemic dysfunction across various layers of the living environment, from the microsystem to the macrosystem. Key triggering factors include economic pressure, family conflict, verbal abuse, and the negative impact of digital technology. The lack of early detection and the high social stigma in Indonesia further exacerbate this risk. Child suicide prevention requires multisectoral synergy through the LIVE LIFE strategy, which includes strengthening emotional resilience from an early age, educating on positive parenting, and providing accessible, child-friendly mental health support services